E13 Retinal changes in patients with huntington's disease. (September 2018) - Kopal, Ales; Dusek, Pavel; Preiningerova, Jana Lizrova; Brichova, Michaela; Ulmanova, Olga; Klempir, Jiri; Roth, Jan
Abstract : Background: Huntington's disease (HD) is a neurodegenerative disorder with dominant motor and neuropsychiatric symptoms. A few studies found that visual symptoms may also be affected in HD. Aims: To assess the structural changes in retina by spectral domain optical coherence tomography (OCT). Methods: 21 patients with genetically verified HD were included in the study (11 males and 10 females, CAG triplet repeats 44.5±2.6 [mean ±standard deviation], age 50.2±10.10.8 years [mean ±standard deviation], disease duration 5.9±3.8 years [mean ±standard deviation]). All patients were assessed by Unified Huntington's disease Rating Scale (UHDRS). Ophtalmological examination included visual acuity (100% contrast), intraocular pressure measurement and fundus examination. Spectral domain OCT was performed to evaluate the peripapillary retinal nerve fiber layer (RNFL) thickness in nasal-superior (NS), nasal (N), nasal-inferior (NI), temporal-inferior (TI), temporal (T), temporal-superior (TS) sectors and with nasal-temporal ratio (N/T) and with papillo-macular bundle. Results: Peripapillary RNFL thickness measurements were performed in 33 eyes of 21 patients. Age, disease duration, the number of CAG triplet repeats, UHDRS total motor score (TMS) and UHDRS total functional capacity (TFC) were tested for a relationship with global RNFL thickness (G) and with RNFL thickness in NS, N, NI, TI, T, TS sectors, N/T ratio and with papillo-macular bundle using a Pearson's r coefficient. Correlations of NS and N/T with disease duration and T with UHDRS TFC and UHDRS TMS were found to be significant. However, no correlation did pass the Bonferroni correction for multiple comparison. Conclusions: We found significant correlations between RNFL thickness in NS and N/T with disease length and between RNFL thickness in T with UHDRS TFC and UHDRS TMS. Patients with HD with longer disease duration had thinner RNFL thickness in NS and N/T. Patients with lower TFC and higher TMS had thinner RNFL thickness in T. Nevertheless, in case of using the Bonferroni correction for multiple comparison, we found no correlation.